Epidemiology, diagnosis, prevention and treatment of catheter-related thrombosis in children and adults. Issue 157 (September 2017) - Baumann Kreuziger, Lisa; Jaffray, Julie; Carrier, Marc
Abstract: In this narrative review, the epidemiology, diagnosis, prevention strategies, and management of catheter-related thrombosis are outlined. Central venous catheters have significantly improved the quality of life of patients requiring chemotherapy, parenteral nutrition, and chronic transfusions. Catheter-related thrombosis (CRT) complicates between 1–5% of inserted catheters, with incidence varying between patient population, catheter type, and vein cannulated. Strategies to prevent CRT, including anticoagulation and locking solutions, have largely been ineffective. Using clinical decision tools and D-dimer testing can limit radiographic testing for patients with suspected CRT. Although most patients with CRT are treated with anticoagulation, the most effective type and duration of treatment have not been established for adults or children. Many unanswered questions remain concerning risk stratification, prevention, and management of CRT. National and international collaborative research networks could be harnessed to perform these much needed studies. Highlights: Catheter-related thrombosis (CRT) occurs in 1–5% of inserted catheters. The Constans score is a clinical prediction rule for upper extremity thrombosis. The most effective type and duration of therapy for CRT has not been established. Treatment of CRT in children is based upon studies in adults.